Effects of fluvastatin, valsartan, and their combination on endothelial function in patients with arterial hypertension and dyslipidemia - T. Sh. Mirilashvili; S. V. Villewalde; Yu. V. Kotovskaya; Zh. D. Kobalava (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of an angiotensin II receptor antagonist (ARA II) valsartan, a statin (fluvastatin XL), and their combination on endothelial function (EF) in patients with arterial hypertension (AH) and dyslipidemia (DLP).Material and methods. In total, 30 patients with untreated, non-complicated Stage I-II AH and DLP IIA or IIB were randomised for 8-week monotherapy with valsartan or fluvastatin XL, with the subsequent addition of the second component, fluvastatin XL or valsartan, respectively.Results. Valsartan monotherapy was associated with a reduced increase in linear blood flow velocity (LFV) during the reactive hyperemia test (RHT) - 177,7+5,8 vs. 170,0+4,9% (p<0,01). At the same time, brachial artery endothelium-dependent vasodilatation (BA EDVD) increased by 14% (p>0,05). Eight-week monotherapy with fluvastatin XL (80 mg/d) was linked to moderate but statistically significant reduction (-2%) in systolic blood pressure (SBP), with no effect on diastolic BP level. In RHT, LFV increase did not change, but EF improved, as manifested in BA EDVD increase. Prolonged combined therapy resulted in further EF improvement.Conclusion. Combined fluvastatin XL and valsartan therapy in patients with untreated Stage I-II AH and DLP IIA or IIB improved EF more effectively than valsartan or fluvastatin XL monotherapy.